Effective implementation of crop diversification strategies for Cambodia, Lao PDR and Vietnam: Insights from past experiences and ideas for new research - Vernooy, Ronnie (Bioversity International, 2015)
The governments of Cambodia and Lao PDR have made strong commitments through the Climate Change Initiative of the Association of Southeast Asian Nations (ASEAN) to integrate mitigation of and adaptation to climate change into their national and sectoral development policies and action plans. Vietnam has also started to address climate-change adaptation at the national and sub-national levels. Governments in the three countries have identified a series of agriculture-based interventions as priorities to strengthen the resilience of smallholder farmers, most notable of which is crop diversification. However, how to practically implement effective policy measures that are of particular benefit to smallholder farmers remains a challenge. Research could contribute to developing a number of pilot initiatives at a sub-national scale to test and assess promising measures. If proven effective, these could then be scaled up under national agricultural policies and the national adaptation programmes of action for climate change (NAPAs). Vietnam does not have a NAPA, but chapter 2 offers a brief analysis of the NAPAs of Cambodia and Lao PDR in terms of the attention paid to crop diversification. It is based on a larger study about NAPAs and aims to explore the extent to which the NAPAs developed by Cambodia and Lao PDR include activities that, directly or indirectly, propose to utilize higher levels of biological diversity in production systems, agricultural research and development. The original study is entitled “Increased biodiversity in agricultural systems and the status of genetic resources for food and agriculture in the ‘National Adaptation Programmes of Action’ (NAPAs).” It will be published in 2015 by Bioversity International.